REST mediates resolution of HIF-dependent gene expression in prolonged hypoxia - Cavadas, Miguel A. S. (2015)
The hypoxia-inducible factor (HIF) is a key regulator of the cellular response to hypoxia which promotes oxygen delivery and metabolic adaptation to oxygen deprivation. However, the degree and duration of HIF-1α expression in hypoxia must be carefully balanced within cells in order to avoid unwanted side effects associated with excessive activity. The expression of HIF-1α mRNA is suppressed in prolonged hypoxia, suggesting that the control of HIF1A gene transcription is tightly regulated by negative feedback mechanisms. Little is known about the resolution of the HIF-1α protein response and the suppression of HIF-1α mRNA in prolonged hypoxia. Here, we demonstrate that the Repressor Element 1-Silencing Transcription factor (REST) binds to the HIF-1α promoter in a hypoxia-dependent manner. Knockdown of REST using RNAi increases the expression of HIF-1α mRNA, protein and transcriptional activity. Furthermore REST knockdown increases glucose consumption and lactate production in a HIF-1α- (but not HIF-2α-) dependent manner. Finally, REST promotes the resolution of HIF-1α protein expression in prolonged hypoxia. In conclusion, we hypothesize that REST represses transcription of HIF-1α in prolonged hypoxia, thus contributing to the resolution of the HIF-1α response.